What is the relationship between family closeness, social support, and adolescent physical activity? Evidence from longitudinal tracking - Li, Hanyu; Zhou, Xielin; Yu, Wanbin (Frontiers in Psychology, 2025)
PurposeUsing a longitudinal cross-lagged design, this study examines the intrinsic relationship between family closeness, social support, and adolescent physical activity.MethodsUsing the Family Intimacy Questionnaire, Social Support Rating Scale (SSRS), and Physical Activity Rating Scale (PARS), a two-phase longitudinal study was conducted on 802 adolescents (52.5% female) with a three-month interval between assessments.Results(1) For adolescents, significant gender differences were found in family closeness, social support, and physical activity (p < 0.01); (2) Correlation analysis revealed positive pairwise correlations among family closeness, social support, and physical activity (all p < 0.01); (3) Cross-lagged analysis indicated that T1 family closeness significantly and positively predicted T2 social support (β = 0.30, p < 0.01), while T1 social support also significantly and positively predicted T2 family closeness (β = 0.30, p < 0.01). Furthermore, T1 family closeness significantly and positively predicted T2 physical activity (β = 0.29, p < 0.01), and T1 physical activity significantly and positively predicted T2 family closeness (β = 0.17, p < 0.01); T1 social support significantly and positively predicted T2 physical activity (β = 0.36, p < 0.01), and T1 physical activity significantly and positively predicted T2 social support (β = 0.22, p < 0.01).Conclusion(1) Significant gender differences exist in family closeness, social support, and physical activity among children and adolescents; (2) Family closeness and social support are positively correlated with adolescent physical activity; (3) Within the adolescent cohort, family closeness and social support cross-predict physical activity over time, while social support and physical activity also cross-predict each other over time.